PENINGKATAN HASIL BELAJAR SISWA KELAS III SD PADA MATA PELAJARAN IPAS MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SD SWASTA HKBP PADANG BULAN MEDAN T.A 2025/2026 - Eka Margareta Sinaga; Sepriana Sinaga; Cicilia Ariadne Sirait; Pernandina Tamba; Cindi Lusiana Pardede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of third-grade students at SD Swasta HKBP Padang Bulan Medan in the Natural and Social Sciences (IPAS) subject, particularly on the topic of Indonesian Landforms. The purpose of this study was to improve students' learning outcomes through the implementation of the Contextual Teaching and Learning (CTL) model. This research employed a Classroom Action Research (CAR) design conducted in two cycles. The participants were 26 third-grade students of SD Swasta HKBP Padang Bulan Medan in the 2025/2026 academic year. Data were collected through learning outcome tests and observation sheets of teacher and student activities. The results showed a significant improvement in students' learning outcomes in each cycle. In the pre-test stage, only 4 students (15.38%) achieved mastery learning with an average score of 44.53. After the implementation of the CTL model in Cycle I, the number of students achieving mastery increased to 9 students (34.61%) with an average score of 63.92. In Cycle II, the number of students achieving mastery learning increased to 20 students (76.92%) with an average score of 77.69. Teacher activity improved from 66% in Cycle I to 86% in Cycle II, while student activity increased from 58% to 80%. These findings indicate that the Contextual Teaching and Learning (CTL) model effectively improves students' learning outcomes by connecting learning materials to students' real-life experiences. The study was considered successful because it achieved the predetermined success indicator, namely a classical learning mastery level of 75%.